The study of METTL14, ALKBH5, and YTHDF2 in peripheral blood mononuclear cells from systemic lupus erythematosus. Issue 9 (25th June 2020) - Luo, Qing; Rao, Jiayue; Zhang, Lu; Fu, Biqi; Guo, Yang; Huang, Zikun; Li, Junming
Abstract: Background: This study was aimed to explore the mRNA expression of m6A "writers" ( METTL3, MTEEL14, and WTAP ), "erasers" ( FTO and ALKBH5 ), and "readers" ( YTHDF2 ) in peripheral blood mononuclear cells (PBMCs) from systemic lupus erythematosus (SLE) patients and investigate the relation between their expressions with clinical features. Methods: In all, 54 SLE patients and 42 healthy controls (HC) were included in the current study. Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was used to investigate the mRNA expression of m6A "writers, " "erasers, " and "readers" in PBMCs from SLE patients and HC. Results: Decreased mRNA expression of MTEEL14, ALKBH5, and YTHDF2 was observed in SLE patients compared with those in HC ( p  < .001). The decreased mRNA expression of METTL14 was associated with white blood cell count (WBC) and monocyte count (M), this decreased mRNA expression of ALKBH5 was associated with C‐reactive protein (CRP), neutrophil percentage (N%), lymphocyte percentage (L%), neutrophil–lymphocyte ratio (NLR), complement 3 (C3), and fever, and the decreased mRNA expression of YTHDF2 was associated with L%, NLR, C3, and fever. In addition, there was a positive correlation between mRNA expression of METTL14, ALKBH5, and YTHDF2 in PBMCs from SLE patients. Importantly, logistic regression analysis revealed that decreased mRNA expression of YTHDF2 was a risk factor for SLE. Conclusion: Taken all together, our findings suggested decreased YTHDF2 that was associated with disease activity may play an important role in the pathogenesis of SLE, METTL14 and ALKBH5 may be concomitantly decreased. Abstract : SLE patients had lower mRNA expression of METTL14, ALKBH5 and YTHDF2 and logistic regression analysis revealed that decreased mRNA expression of YTHDF2 was a risk factor for SLE